Effect of Additional Markisa Rind Pektin on The Mechanical Properties of Biodegradable Plastic Garut Starch - Dwiana Pratiwi; Endaruji Sedyadi (Gontor AGROTECH Science Journal, 2020)
plastics. The manufacture of biodegradable plastics from starch arrowroot  with addition of pectin passion fruit's rind and glycerol plasticizer has been done. This study aimed to understand the impact of the addition of pectin passion fruit’s rind on the mechanical properties of the biodegradable plastic. Biodegradable plastic characterized by its mechanical properties include thickness, tensile strength, elongation, and young modulus. The variations of the pectin passion fruit's rind used were 0, 1, 2, 3, and 4 grams. The results showed that the addition of pectin passion fruit’s rind tended to lose tensile strength, but increased elongation of biodegradable plastic. The highest elongation was 16.6657% with the addition of 3 grams of pectin passion fruit's rind, but decreased the tensile strength by 4.5602 Mpa